Recombinant adenovirus-p53 (Gendicine) sensitizes a pancreatic carcinoma cell line to radiation - Li, Jinluan; Pan, Jianji; Zhu, Xianggao; Su, Ying; Bao, Lingling; Qiu, Sufang; Zou, Changyan; Cai, Yong; Wu, Junxin; Tham, Ivan W.K. (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: In this study, we examine the effects of recombinant adenovirus-p53 (rAd-p53) on the pancreatic carcinoma cell line SW1990. Specifically, we determine if expression of rAd-p53 sensitizes these cells to radiation. Methods: Following transfection of SW1990 cells with rAd-p53, we measured expression of P53, P21 and Bax by immunocytochemistry. Both transfected and control cell lines were irradiated with a range of doses, and the survival fractions (SF) were calculated. Dose survival curves were constructed and modeled for comparison. Results: Transfection of SW1990 cells with rAd-p53 resulted in increased expression of P53, P21 and Bax in a time-dependent manner. At 96 h after transfection, 89.92% of cells expressed P53, 56.8% expressed P21, and 76.50% expressed Bax. The SF following radiation was lower in the rAd-p53 transfected cells compared to the control cells, suggesting that rAd-p53 sensitizes SW1990 cells to radiation (D0 for the experimental and control groups was 2.199 and 2.462, respectively). Conclusions: Use of the adenoviral vector is an effective means of transfecting SW1990 cells with wild-type P53, and this sensitizes the cell line to irradiation. This work suggests that combining rAd-p53 with radiation therapy in pancreatic cancer may be therapeutically beneficial.